A bibliometric review on the inter-connection between climate change and horticulture sector - Ananya Pati; Srija Das; Kamran Haider Zaidi; Mary Tahir (Discover Agriculture)
Abstract Horticulture crops are extremely vulnerable to climate change all over the world. The changes in seasonality, temperature extremity, and unpredictable rainfall conditions directly influence the phenological stages of horticulture crops. The present study focuses on horticultural fruit crops, changes in the trend of climate indices, and the various impacts faced by the farmers. This study has taken into consideration the research work of worldwide scholars, published between the periods of 2000 and 2023 that is indexed in the Scopus database. This study draws attention to the year-wise publication numbers, highly cited papers, country-wise distribution of documents, and frequently used keywords in the Scopus dataset. A total of 443 articles from 220 journals are found to be most relevant based on the present topic. The result shows that, among the publications from 57 countries, the highest number of publications came from India with 293 publications, followed by Germany with 156 publications, and China with 152 publications. The highest number of citations is received by the publications from Germany, followed by the USA and Australia. Climate change, phenology, temperature, horticulture, and dormancy are some of the frequently used keywords in the present database. The Scopus database is analysed using VOSviewer software and RStudio. Based on this bibliometric analysis, it appears to be a new research topic that has gained attention in the last decade. India holds a significant global position in this field, although developed countries continue to lead in conducting more relevant and impactful research.